(untitled) (Communications in Computational Physics, 2007)
We investigate the behavior and sensitivity of the frozen mode phenomenon in finite structures with anisotropic materials, including both magnetic materials and non-normal incidence. The studies are done by using a high-order accurate discontinuous Galerkin method for solving Maxwell's equations in the time domain. We confirm the existence of the phenomenon also in the time-domain and study carefully the impact of the finite crystal on the frozen mode. This sets the stage for a thorough study of the robustness of the frozen mode phenomenon, resulting in guidelines for which design parameters are most sensitive and acceptable tolerances.